Nanoporous ?-cyclodextrin-containing Silicas: Synthesis, Structure and Properties - L. A. Belyakova; D. Yu. Lyashenko; L. S. Dzyubenko; O. M. Shvets (Хімія, фізика та технологія поверхні)
Nanoporous b-cyclodextrin-containing silicas which differ in functional substituents of wide edge of attached cyclic oligosaccharide molecules (alcohol, bromoacetyl, thiosemicarbazidoacetyl groups) were synthesized. Сhemical composition of surface layer of organosilicas and their sorptional parameters were determined using IR spectroscopy, isotherms of nitrogen ad-desorption, elemental, chemical and thermogravimetric analyses. Ranges of thermal and chemical stability of synthesized b-cyclodextrin-containing silicas were defined; a method of organosilicas regeneration was proposed. Activation energies of water removal from the inner cavities of ?-cyclodextrins and from the surface of functional organosilicas were calculated. Distribution and selectivity coefficients for sorption of mercury(II), copper(II), lead(II), cadmium(II), and zinc(II) cations were computed.